Literature Study on Financing Risk Management Research in Non-Bank Institutions: Baitul Mal Wat Tamwil - Elidaman Waruwu (Eduvest - Journal of Universal Studies, 2024)
Baitul Mal Wat Tamwil (BMT) plays an important role in serving the financial needs of people who have not been reached by conventional banks, especially the lower economic strata. Along with the growth of BMT in Indonesia since 1984, the main challenge faced is the financing risk that can threaten the sustainability of operations. Previous research on financing risk management in BMT has been widely conducted. However, there has been no literature review on the topic. Therefore, this article aims to conduct a literature review of the results of financing risk management research on BMT. The review was performed on the research results published in national scientific journals indexed in Google Scholar as many as ten articles. The results of the review show that trained human resources play an essential role in risk management in BMT; BMT does not yet own complete regulation and standardized risk control system; submission of financing applications at BMT is carried out by the procedure; Problematic financing is handled gradually starting from a familial approach, the application of rescheduling and restructuring, then the last step is legal settlement. The implication of this study is that increasing human resource capacity and strengthening regulations can improve the sustainability and competitiveness of BMT as a sharia microfinance institution in Indonesia